Learn Raspberry Pi programming with Python - Donat, Wolfram (TECHNOLOGY IN ACTION series, 2018)
'Learn raspberry pi programming with Python' show you how to programyour nifty new $35 computer using Python to make fun, hands-on projects, such as a web spider, a weather station, a media server and more.